Ananta Toer in Malaysia: Humanist Ideology, Reception History, and His Position in the Nusantara Literary Discourse - Awang Pawi, Awang Azman; Sahiddan, Nurhanis; Muhamad Nik Affendi Pi, Nik Rafidah (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
This paper Pramoedya Ananta Toer, a major literary figure in Indonesia, has made significant contributions to the Malay literary world through works that champion social justice, nationalism, and historical consciousness. In Malaysia, his works have found a place in educational and academic domains despite being banned or rejected in his home country during the New Order regime. This study traces the reception history of Pramoedya’s works in Malaysia, identifies the ideological factors shaping this acceptance, and analyses how he has been appreciated by Malaysian scholars. Using a qualitative approach combining in-depth interviews, textual analysis, and documentary research, this article argues that Pramoedya’s contributions are valued not merely through the lens of political controversy, but from perspectives of humanism, postcolonial values, and regional literary solidarity within the Malay world.